Dinámica de crecimiento, mortandad y supervivencia de la especie Aspidosperma schultesii Woodson "quillobordon", en la plantación 13 del CIEFOR - Puerto Almendra, Loreto - Perú. 2021 - Maca Davila, Peter´s (2021)
The study was carried out in Plot No. 13 of CIEFOR - Puerto Almendras, where 200 Aspidosperma schultesii Woodson “quillobordon” plants were planted. The plants were sown every 5 meters and in 10 strips. The greatest increase in diameter was presented by band 2 with a value of 0.04 mm between the first and last evaluation. The greatest increase in height was presented by band 1 with a value of 3.70 cm between the first and last evaluation. The bands with the least increase were 9 with 1.51 cm and band 10 with 1.71 cm. Likewise, the strip that presented the highest total height was strip 5 with 52.65 cm in the first evaluation and 54.32 in the last evaluation. For the increase in diameter and height, the “F” test with 95% probability of confidence indicates that there is a statistical difference between the evaluated treatments (p = 0.000). Survival ranged between 80% and 100% while mortality ranged between 5 and 20%. A total of 9 strips show values between 1.1 to 1.5 (Good Quality); as long as band 8 presents an Excellent Quality Coefficient (1.0). Similar studies are needed with other native forest species in CIEFOR - Puerto Almendras.